Numerical simulation for longitudinal and transverse coupling motion in compact electron beam simulator for heavy ion inertial fusion. (July 2015) - Kikuchi, Takashi; Horioka, Kazuhiko; Takahashi, Kazumasa; Sasaki, Toru; Aso, Tsukasa; Harada, Nob.
Abstract: For heavy-ion beam driven inertial confinement fusion, space-charge-dominated beams are studied by a compact experimental device, scaled by electrons instead of heavy ions. In this study, space charge effect is investigated numerically in the compact electron beam simulator. Modeling of the compact beam simulator is studied, and a molecular dynamics simulation, which represent a so-called particle–particle model, is applied to the calculation of particle dynamics in three-dimensional space. A longitudinal-transverse coupling motion is observed in the multi-particle simulation result. Highlights: Compact beam simulator for heavy ion inertial fusion was numerically modeled. Multi-particle simulation code was developed for the electron beam compact simulator in 3D space. The calculation results show the longitudinal pulse compression with solenoidal transverse confinement. The calculation results show the expansion of beam radius due to space charge effect. The longitudinal-transverse coupling motion was observed in the compact simulator.